PENGARUH MODEL WEBBED TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA TEMA ROKOK DI SMP NEGERI 24 PONTIANAK - Erma Suriani; Eny Enawaty; Rachmat Sahputra (EduChem, 2023)
The aims of this research were to determine 1) the differences in student learning outcomes who taught using the webbed model with students who taught using conventional models 2) the influence of the webbed model with the theme of cigarettes was carried out in class VIII C and VIII D of SMP Negeri 24 Pontianak. The form of the research used was quasi-research with a non-equivalent control group design. The research sample was class VIII C as an experimental class and class VIII D as a control class. Data collection tools that was used in this study were tests. Based on the result of statistical test data using the Independent Sample T-Test, obtained a value of 0,000 indicates that the value of Asymp.Sig (2-tailed) < 0.05, which means there were significant differences in learning outcomes between the experimental class and the control class students. The effect of the webbed model on student learning outcomes after being analyzed with the effect size formula was 1.42 which means it provided an increase in learning outcomes of 42.22%. Based on the hypothesis test it can be concluded that learning with a webbed model can improve student learning outcomes.Keyword : Webbed Model, Learning Outcomes, Cigarettes